Pomoč in njene meje v kazenskem pravu - Ambrož, Matjaž (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2011)
The article analyses aiding and abetting as a form of participation in criminal law. Firstly, the attention is paid to the time-limits of aiding and abetting, which, according to the author, have to be defined narrowly, and must not be stretched over the formal completion of the act. Another crucial question is delimitation of aiding and abetting and co-perpetration. The author argues that aiding and abetting can be, however, it must not be a necessary precondition for success of the act. In this respect he critically analyses some judicial decisions in which typical acts of aiding and abetting are held for co-perpetration, since they are deemed as necessary precondition for the criminal offence. Finally, the article addresses sentencing, where the author pleads for obligatory reduction of punishment in cases of aiding and abetting.
Keywords: criminal law; kazensko pravo; participation; kazniva dejanja; aiding and abetting; instigation; storilci; sodelovanje; co-perpetration; culpability; pomoč; intent; udeležba; napeljevanje; sostorilstvo; krivda; naklep